Nanometer scale mapping of cobalt in Al-doped ferromagnetic Zn 0.7Co0.3O thin film - RODE, KARSTEN (My University, 2006)
There has been a renewed interest in zinc oxide in the materials science community after it was shown to be ferromagnetic when doped with cobalt. However, it has remained difficult to tell whether the origin of the phenomenon was intrinsic or due to secondary phases. Here, we examine with analyti- cal transmission electron microscopy the distribution of cobalt in a thin film of ferromagnetic Al-doped Zn 0 . 7 Co 0 . 3 O that we have grown by pulsed laser deposition on alumina. We show that precipitation of a secondary phase does occur, but that it concerns less than 10% of the cobalt atoms. The precipitates appear to be made of hexagonal metallic Co, and their average diameter is 4 nm. Their magnetism could be the reason for the low measured Curie temperature of the sample (50 K). On the other hand, the overall measured magnetization of 0.7 μ B per cobalt atom suggests that the Co atoms in solution are at the origin of most of the signa
PUBLISHED
Keywords: 68.37.Lp Transmission electron microscopy (TEM) (including STEM, HRTEM, etc.) – 75.50.Pp Magnetic semiconductors; 68.37.Lp Transmission electron microscopy (TEM) (including STEM, HRTEM, etc.) – 75.50.Pp Magnetic semiconductors